(Im)possibilities of Autonomy: Social Movements in and beyond Capital, the State and Development. - Böhm, Steffen; Dinerstein, Ana C.; Spicer, André (Social Movement Studies, 2010)
In this paper we interrogate the demand and practice of autonomy in social movements. We begin by identifying three main conceptions of autonomy: (1) autonomous practices vis-a-vis capital; (2) self-determination and independence from the state; and (3) alternatives to hegemonic discourses of development. We then point to limits associated with autonomy and discuss how demands for autonomy are tied up with contemporary re-organizations of: (1) the capitalist workplace, characterized by discourses of autonomy, creativity and self-management; (2) the state, which increasingly outsources public services to independent, autonomous providers, which often have a more radical, social movement history; and (3) regimes of development, which today often emphasize local practices, participation and self-determination. This capturing of autonomy reminds us that autonomy can never be fixed. Instead, social movements' demands for autonomy are embedded in specific social, economic, political and cultural contexts, giving rise to possibilities as well as impossibilities of autonomous practices.